2013
DOI: 10.1016/j.indcrop.2012.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of Withania ashwagandha sp. novo (Solanaceae)

Abstract: Withania ashwagandha Kaul (Solanaceae) is an annual plant species of immense medicinal importance. It is a repository of a large number of pharmacologically active secondary metabolites known as withanolides. Evidence for the delimitation of the species from W. somnifera has been provided by our group using multidisciplinary approaches. Knowledge of reproductive biology of medicinal plants is crucial for improvement, effective conservation and management plans to evolve genetically superior varieties. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…In a similar study by Aleemullah et al [18] which analyzed the phenology of Capsicum annuum flowering, it was observed that the anthesis was presented with greater frequency during the morning. In a study of the reproductive biology of Jatropha curcas, Rincón-Rabanales et al [6] found that the flowers, both masculine and feminine, begin to open at 8:00 h, and that the maximum aperture of the flowers is registered at 9:00 h, while Mir et al [5], studying the reproductive biology of Withania ashwagandha sp. Novo (Solanaceae), they observed that the anthesis occurred in an interval between 8:00-11:00 h. These results allow the inference that the more usual anthesis in several species including a Capsicum chinense is that flowers open in the morning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar study by Aleemullah et al [18] which analyzed the phenology of Capsicum annuum flowering, it was observed that the anthesis was presented with greater frequency during the morning. In a study of the reproductive biology of Jatropha curcas, Rincón-Rabanales et al [6] found that the flowers, both masculine and feminine, begin to open at 8:00 h, and that the maximum aperture of the flowers is registered at 9:00 h, while Mir et al [5], studying the reproductive biology of Withania ashwagandha sp. Novo (Solanaceae), they observed that the anthesis occurred in an interval between 8:00-11:00 h. These results allow the inference that the more usual anthesis in several species including a Capsicum chinense is that flowers open in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three times evaluated (0, 24 and 48 h), the best time for use was the time of harvesting (0 h), given that the pollen presented a greater percentage of viability (88%) and a greater number of seeds per fruit (NSF), although the percentage of fruit set (%FS) was low ( Table 9 and Figure 7). Mir et al [5] concluded that low fructification in cross-pollination after emasculation is an indicator of partial fixation of autogamy in the Withania ashwagandha sp. Novo (Solanaceae).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Withania somnifera also known as Ashwagandha, Indian ginseng, poison gooseberry or winter cherry belongs to family Solanaceae and is a cross pollinated crop with chromosome number of 2n=48 (Nigam and Kandalkar, 1995) and is one of the important medicinal plants (Mir et al, 2013). It is a hardy and drought tolerant perennial shrub and grows naturally under subtropical dry climate (with an average rain fall of 600-750 mm) in well drained, sandy loam or light red soils that have a pH of 7.5 to 8.0.…”
Section: Introductionmentioning
confidence: 99%
“…It is an annual selffertilizing herb with restricted geographic distributed growing exclusively as small-cultivated populations only in drier regions of India (Mir et al 2013). Recently, it has been delineated form wild germplasm of W. somnifera using multidisplinary genome diagnostic approaches (Mir et al 2010;Kumar et al 2011).…”
Section: Introductionmentioning
confidence: 99%